The dependent correlation between soil multifunctionality and bacterial community across different farmland soils - Liu, Jing; Gul Wazir, Zafran; Hou, Guo-Qin; Wang, Gui-Zhen; Rong, Fang-Xu; Xu, Yu-Zhi; Liu, Kai; Li, Ming-Yue; Liu, Ai-Ju; Liu, Hong-Liang (Frontiers in Microbiology, 2023)
Microorganisms play a critical role in soil biogeochemical cycles, but it is still debated whether they influence soil biogeochemical processes through community composition and diversity or not. This study aims to investigate variation in bacterial community structure across different soils and its correlation to soil multifunctionality. Soil samples were collected from five typical farmland zones along a distinct climatic gradient in China. The high-throughput sequencing (Illumina MiSeq) of 16S rRNA genes was employed to analyze bacterial community composition in each soil sample. Multivariate analysis was used to determine the difference in soil properties, microbial community and functioning, and their interactions. Cluster and discrimination analysis indicated that bacterial community composition was similar in five tested soil samples, but bacterial richness combined with soil enzyme activities and potential nitrification rate (PNR) contributed most to the differentiations of soil samples. Mantel test analysis revealed that bacterial community composition and richness were more significantly shaped by soil nutrient conditions and edaphic variables than bacterial diversity. As for soil multifunctionality, soil microbial community level physiological profiles were little affected by abiotic and biotic factors, while soil enzymes and PNR were also significantly related to bacterial community composition and richness, in addition to soil N and P availability. Cumulatively, soil N and P availability were one of the major factors modifying bacterial community structure and function in different farmland soils. Therefore, in the future it should be considered for the role of fertilization in the modification of bacterial community and the consequent control of nutrient cycling in soil.